Does Management Really Matter? And If so, to Who?; Comment on "Management Matters: A Leverage Point for Health Systems Strengthening in Global Health" - Delanyo Dovlo (Kerman University of Medical Sciences, 2016)
The editorial is commendable and I agree with many of the points raised. Management is an important aspect of health system strengthening which is often overlooked. In order to build the capacity of management, we need to consider other factors such as, the environment within which managers work, their numbers, support systems and distribution. Effective leadership is an issue which cannot be overemphasized as part of management capacity in resource deprived settings as difficult settings require leadership skills in order to achieve managerial success. A primary issue of importance highlighted in the editorial is country ownership of management effectiveness initiatives, which may be very difficult when the health sector is dependent on support and funding from donors and influential partners, who drive change often without a good understanding of the context. How partners finance health programmes is another dilemma as it can distract from locally determined priorities. Further research should help us to understand better what works and under different settings.